DAMPAK ERA NEW NORMAL TERHADAP PEKERJA SEKTOR INFORMAL - Lilis Sri Sulistiani (Universitas Halu Oleo, 2021)
The impact of the Covid-19 pandemic on workers in the informal sector is a decrease in income and production capacity, as well as a reduction in labor. This study aims to analyze the impact of implementing the new normal era on informal sector workers and formulate strategies for surviving the pandemic.The research method used in this paper is descriptive qualitative method by applying literature study.The results of the study show that the implementation of the first new normal era has an impact on business situations that are volatile, uncertain, complicated and confusing. Second, the impact of the pandemic on business people has resulted in limited resources. Third, changes in consumer behavior who prefer online shopping. So that the economic recovery of informal sector workers in the new normal era requires various strategies, namely: the existence of occupational health and safety insurance, the ability to work together, the ability to adapt services to changes in consumer behavior, to have innovation and creativity in running a business.